Patent foramen ovale and stroke: current evidence and treatment options. Issue 1 (February 2020) - Favilla, Christopher G.; Messé, Steven R.
Abstract : Purpose of review: Recent data have changed the landscape of patent foramen ovale (PFO) closure for secondary stroke prevention. This review synthesizes the data and provides a framework for optimal management of stroke patients with PFO. Recent findings: The cumulative evidence indicates that PFO closure reduces the risk of recurrent stroke in carefully selected young cryptogenic stroke patients, with an annualized risk reduction of ∼0.6%. The benefit of PFO closure is particularly evident in patients with embolic appearing strokes, large right-to-left shunt, or an associated atrial septal aneurysm. There may be little or no benefit in patients with small deep infarcts, a small PFO, or an indication for long-term anticoagulation. Closure is accompanied by a small risk of major procedural complication and atrial fibrillation. Summary: The annual risk of stroke from PFO is low relative to other stroke mechanisms, but the life-time cumulative risk in young patients who have experienced a prior stroke may be substantial, in which case the absolute benefit of closure is likely impactful. PFO is highly prevalent in the general population, present in about one in four adults, and should not be considered to be the cause of the stroke until a thorough workup has excluded alternative mechanisms.